UKRAINIAN AMATEUR THEATER IN KOLOMYIA OF 1848-1850 - Pylypchuk, R.Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article examines the development of Ukrainian amateur theater in Kolomyia of 1848-1850, reveals the history of the stage play “The Girl Preparing to Get Married” by Ivan Ozarkevych that is a remake of the remarkable famous Ivan Kotliarevskiy’s play “Natalka From Poltava”. Literary and theatrical adaptation of another drama of the author, “Moskal the Wonder”, entitled “Zhovnir the Wonder”, is reviewed also. The article describes how these stage versions promoted theater art in Western Ukraine.